Serum magnesium levels during pregnancy and their correlation with maternal demographic characteristics: A cross-sectional study - Burhanedin Meerany, Rose; Abd Ezat, Shayma; Omer Jaafar, Shelan; P. Shabila, Nazar; Kareem Alalaf, Shahla (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: The rate of low magnesium levels in pregnancy varies significantly between regions, shaped by dietary practices, socioeconomic factors, and healthcare access. This study aimed to determine the prevalence of hypomagnesaemia in pregnant women attending a tertiary public hospital and any maternal associated factor in relation to magnesium levels. Methods: A cross-sectional study was conducted on 930 pregnant women across all trimesters at Maternity Teaching Hospital, Erbil, Kurdistan Region, Iraq, from 3rd January 2023 to 3rd January 2024. Serum magnesium concentrations (mg/dL) were determined using the Cobas Integra analyzer. These levels were correlated with demographic characteristics and weight. Results: The mean serum magnesium level was 1.86±0.22 mg/dL (median 1.88, range 0.47-2.7 mg/dL). Hypomagnesemia was observed in 4.3% (n=40) and hypermagnesemia in 3.3% of participants. Serum magnesium levels showed a trend towards decreasing with advancing gestational age, although differences between trimesters were statistically significant. No significant association was found between hypomagnesemia and educational level or occupation. Conclusion: Hypomagnesemia was infrequent in pregnant women at the studied hospital and was not linked to education, socioeconomic status, or body weight.